The Inspection of Education in the Canary Islands - Gregorio Cabrera Déniz (ADIDE Federación, 2010)
The Inspectorate of Education on the Canary Islands (Spain). As if it were a historical account of it, the author describes the performance of the Inspectorate of Education on the Canary Islands since its beginning, in the middle of the 19th century, until the present day.